Serum and Urinary Values of CA 19-9 and TGFß1 in a Rat Model of Partial or Complete Ureteral Obstruction - Lopes, Roberto Iglesias; Dénes, Francisco Tibor; Bartolamei, Matheus Gesualdo; Reis, Sabrina; Sanches, Talita Rojas; Leite, Kátia Ramos; Srougi, Miguel; Seguro, Antônio Carlos (European Journal of Pediatric Surgery, 2015)
Introduction Abnormal levels of serum and urinary markers occur in the presence of renal damage associated to obstructive uropathy. Urinary and serum transforming growth factor beta 1 (TGFß1) and carbohydrate antigen (CA 19-9) have not yet been evaluated in an experimental model of obstructive uropathy.Material and Methods Rats were divided into seven groups: reference, sham operation, unilateral nephrectomy, complete unilateral ureteral obstruction, partial unilateral ureteral obstruction, partial bilateral ureteral obstruction, and unilateral nephrectomy with contralateral partial ureteral obstruction. Kidney and ureter morphometry, TGFß1 and CA 19-9 serum and urinary concentrations and CA 19-9 renal tissue expression were analyzed. Correlation of these markers to complete, partial obstruction, or unobstructed groups was performed.Results Pathological findings correlated positively with the degree of ureteral obstruction, but negatively with urinary CA 19-9 levels. Marked underexpression of CA 19-9 was observed in kidneys with complete ureteral obstruction. No statistically significant differences were found for urinary and serum TGFß1 and also for serum CA 19-9.Conclusion Urinary CA 19-9 correlated negatively with ureteral obstruction grade. Immunohistochemistry depicted CA 19-9 expression on epithelial tubular cells cytoplasm, suggesting renal origin. Serum and urinary TGFß1 did not show alterations in response to severity and length of urinary obstruction, which might be associated with less intense renal remodeling.
Keywords: urinary obstruction; CA 19-9; TGFß1; ureter; rat